Methotrexate, an anti-inflammatory drug, inhibits Hepatitis E viral replication - Akash Kumar; Preeti Hooda; Anindita Puri; Radhika Khatter; Mohammed S. Al-Dosari; Neha Sinha; Mohammad K. Parvez; Deepak Sehgal (Taylor & Francis Group, 2023)
Hepatitis E Virus (HEV) is a positively oriented RNA virus having a 7.2 kb genome. HEV consists of three open reading frames (ORF1-3). Of these, ORF1 codes for the enzymes Methyltransferase (Mtase), Papain-like cysteine protease (PCP), RNA helicase, and RNA-dependent RNA polymerase (RdRp). Unavailability of a vaccine or effective drug against HEV and considering the side effects associated with the off-label use of ribavirin (RBV) and pegylated interferons, an alternative approach is required by the modulation of specific enzymes to prevent the infection. HEV helicase is involved in unwinding the double-stranded RNA, RNA processing, transcriptional regulation, and pre-mRNA processing. Therefore, we screened FDA-approved compounds from the ZINC15 database against the modelled 3D structure of HEV helicase and found that methotrexate and compound A (Pubchem ID BTB07890) inhibit the NTPase and dsRNA unwinding activity leading to inhibition of HEV RNA replication. This may be further authenticated by in vivo study.